Influence of HVOF parameters on the corrosion and wear resistance of WC-Co coatings sprayed on AA7050 T7 - Magnani, M. [UNESP]; Suegama, P. H. [UNESP]; Espallargas, N.; Dosta, S.; Fugivara, Cecilio Sadao [UNESP]; Guilemany, J. M.; Benedetti, Assis Vicente [UNESP] (Elsevier B.V. Sa, 2008)
Thermal spray WC-based coatings are widely used in the aircraft industry mainly for their resistance to wear, reworking and rebuilding operations and repair of worn components on landing gear, hydraulic cylinders, actuators, propeller hub assemblies, gas turbine engines, and so on. The aircraft industry is also trying to use thermal spray technology to replace electroplating coatings such as hard chromium. In the present work, WC-Co coatings were built up on an AA 7050 aluminum alloy using high velocity oxygen fuel (HVOF) technology and a liquid nitrogen cooling prototype system. The influence of the spray parameters (standard conditions, W19S, increasing the oxygen flux, W19H, and also increasing the carrier gas flux, W19F) on corrosion, friction, and abrasive wear resistance were also studied. The coatings were characterized using optical (OM) and scanning electron (SEM) microscopy, and X-ray diffraction (XRD). The friction and abrasive wear resistance of the coatings were studied using Rubber Wheel and Ball on Disk tests. The electrochemical studies were conducted using open-circuit potential (E(oc)) measurements and electrochemical impedance spectroscopy (EIS). Differences among coated samples were mainly related to the variation of the thermal spray parameters used during the spray process. No significant differences were observed in the wear resistance for the coatings studied, and all of them showed a wear rate around 10 times lower than that of the aluminum alloy. The results of mass loss and wear rate were interpreted considering different mechanisms. Comparing the different spray parameters, the oxygen flux (higher flame temperature) produced the sample which showed the highest corrosion resistance in aerated and unstirred 3.5% NaCl solution. Aluminum ions were detected on the surface almost immediately after the immersion of samples W19S and W19F in chloride solution, showing that the electrolyte reached the substrate and galvanic corrosion probably occurred. For sample W19H, aluminum ions were not detected even after 120 min of immersion in NaCl solution. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: corrosion; electrochemical; thermal spray; WC-Co; aluminum alloy; wear